Prostate health index significantly reduced unnecessary prostate biopsies in patients with PSA 2‐10 ng/mL and PSA >10 ng/mL: Results from a Multicenter Study in China. Issue 11 (30th June 2017) - Na, Rong; Ye, Dingwei; Qi, Jun; Liu, Fang; Helfand, Brian T.; Brendler, Charles B.; Conran, Carly A.; Packiam, Vignesh; Gong, Jian; Wu, Yishuo; Zheng, Siqun L.; Mo, Zengnan; et al.
Abstract : Background: The performance of prostate health index ( phi ) in predicting prostate biopsy outcomes has been well established for patients with prostate‐specific antigen (PSA) values between 2 and 10 ng/mL. However, the performance of phi remains unknown in patients with PSA >10 ng/mL, the vast majority in Chinese biopsy patients. We aimed to assess the ability of phi to predict prostate cancer (PCa) and high‐grade disease (Gleason Score ≥7) on biopsy in a Chinese population. Methods: This is a prospective, observational, multi‐center study of consecutive patients who underwent a transrectal ultrasound guided prostate biopsy at four hospitals in Shanghai, China from August 2013 to December 2014. Results: In the cohort of 1538 patients, the detection rate of PCa was 40.2%. phi had a significantly better predictive performance for PCa than total PSA (tPSA). The areas under the receiver operating characteristic curve (AUC) were 0.90 and 0.79 for phi and tPSA, respectively, P < 0.0001. A considerable proportion of patients in the cohort had PSAs >10 ng/mL ( N = 838, 54.5%). The detection rates of PCa were 35.9% and 57.7% in patients with tPSA 10.1‐20 and 20.1‐50 ng/mL, respectively. The AUCs of phi (0.79 and 0.89, for these two groups, respectively) were also significantly higher than tPSA (0.57 and 0.63, respectively), both P < 0.0001. If a phi ≤35 was used as the cutoff, 599/1538 (39%) biopsies could have been avoided at a cost of missing small numbers of PCa patients: 49 (7.93%) PCa patients, including 18 (3.69%) high‐grade tumors. Conclusions: Results from this study suggest that phi can be used to predict PCa and high‐grade disease in Chinese men with high PSA levels (>10 ng/mL).